Paleta 5 a handbook for visual artists. (National Commission for Culture and the Arts, 2002)
Provides a listing of places, events and institutions concerned with Philippine arts. The work is aimed to help Filipino artists expose their craft to a wider audience and meet others who share their passion. This issue contains sections written in Filipino and an additional "printmaking" section.